Collapse prediction and creep effects - Lourenço, Paulo B. (2008)
The recent collapse of famous historical constructions attributed mainly to the time-dependent behaviour of masonry has driven the attention of the technical community over this issue. Numerical analyses in which units and mortar are individually represented have proven to be of great interest to understand the phenomena at the level of the masonry constituents. Nevertheless, before analysing the influence of long-term effects, it is important that numerical models are able to adequately reproduce the behaviour under short-term compression as it provides a solid basis to correctly capture the response under sustained stresses. Reproduction of short-term behaviour remains, however, unresolved in literature. A contribution is given in the present paper by considering a standard continuum model and a discrete particle model to represent units and mortar. The particle model has showed clear advantages. In addition, the results of an experimental investigation on the creep behaviour of regular ancient masonry including both short-term and long-term creep tests are provided together with a careful discussion of the results.